Awareness of feeding patterns in first-time mothers - KAPOOR, Ms.PRIYA; DHARMADHIKARI, Ms. GAYATRI; SALUNKE, Ms. VAISHNAVI (Indian Journal of Child Health, 2022)
Background: Feeding is a vital source of energy and a necessity for survival. It is pivotal that mothers of new-born are aware of correct feeding patterns as it may impact the feed and health of the infant. The present study aimed to explore the awareness of various breastfeeding and bottle-feeding patterns in first-time mothers of infants up to 6 months of age. Materials and Methods: The participants in the study were 56 first-time mothers with infants